2008
DOI: 10.1002/art.23799
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant resveratrol protects against chondrocyte apoptosis via effects on mitochondrial polarization and ATP production

Abstract: Objective. To determine the effects of the antioxidant resveratrol on the functions of human chondrocytes in osteoarthritis (OA).Methods. Chondrocytes and cartilage explants were isolated from OA patients undergoing knee replacement surgery. Effects of resveratrol in the presence or absence of interleukin-1␤ (IL-1␤) stimulation were assessed by measurement of prostaglandin E 2 (PGE 2 ) and leukotriene B 4 (LTB 4 ) synthesis, cyclooxygenase (COX) activity, matrix metalloproteinase (MMP) expression, and proteogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 48 publications
5
94
0
3
Order By: Relevance
“…Moreover, resveratrol was defensive to the IL-1b-induced catabolic effects of chondrocytes by elevating proteoglycan synthesis, suppressing COX-2 expression and enzyme activity, and decreasing production of MMPs 1, 3, and 13 [18]. A vivo study demonstrated that intraarticular injections of resveratrol reduced the severity of cartilage lesions by histologic examination in the experimental OA model [19].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, resveratrol was defensive to the IL-1b-induced catabolic effects of chondrocytes by elevating proteoglycan synthesis, suppressing COX-2 expression and enzyme activity, and decreasing production of MMPs 1, 3, and 13 [18]. A vivo study demonstrated that intraarticular injections of resveratrol reduced the severity of cartilage lesions by histologic examination in the experimental OA model [19].…”
Section: Discussionmentioning
confidence: 93%
“…These results revealed that S1P protects cartilage degradation from inflammatory cytokineinduced GAG degradation via S1P 1 receptor activation. PGE 2 , which originates from the activation of the COX pathways, is produced by OA chondrocytes and may promote matrix degeneration (19,20). In ex vivo cultures of cartilage explants, the production of PGE 2 was increased by the stimulation of IL-1β in the supernatants of the conditioned media (Fig.…”
Section: S1p Protects Cartilage Explants From Il-1-induced Gag Lossmentioning
confidence: 99%
“…Resveratrol has received tremendous attention over the past couple of decades because of its benefits in several human disease models, including antioxidant effect, anti-inflammatory effect, immune regulation, and cancer chemoprevention [8][9][10]. Recent studies have shown that resveratrol also has good anti-inflammatory effects in rats with osteoarthritis [8,11]. Sodium alginate is a common pharmaceutic adjuvant with antioxidative and immunomodulatory property [12][13][14].…”
Section: Introductionmentioning
confidence: 99%